MO266URINARY TRANSFERRIN AND IGG EXCRETIONS PREDICT TUBULOINTERSTITIAL LESIONS IN PATIENTS WITH IGA NEPHROPATHY. (29th May 2021) - Elena, Saganova; Galkina, Olga; Sipovskii, Vasiliy; Smirnov, Alexei
Abstract: Background and Aims: IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide and is a frequent cause of end-stage renal disease. The best predictors of progression are histologic parameters. Nevertheless, there is a pressing need to identify suitable noninvasive biomarkers in IgAN, to aid with diagnosis, treatment decisions, and prediction of the disease progression. Our aim was to assess diagnostic value of urinary excretions of transferrin and IgG in prediction of morphological lesions in patients with IgAN. Method: 37 patients [19 female, age Me 33 (25; 48) years] with biopsy proven IgAN and without acute kidney injury, infectious diseases, severe heart failure, respiratory insufficiency, cancer were included in the study. 24-hour urinary excretions of transferrin (uTr), IgG (uIgG) were measured by immunoturbidimetric method (Furuno CA-90, Furuno Electric Co., Ltd., Japan). Tubulointerstitial fibrosis (TIF) and tubular atrophy (TA) were assessed semi-quantitatively (0-lesions absent; 1-mild focal tubular and interstitial lesions; 2-moderate tubular and interstitial lesions; 3-diffuse tubular and interstitial lesions). All patients consistently were separated into two groups according to the degree of each morphological lesion (TIF or TA): "mild" (TIF or TA grade 0 or 1) and "severe" (TIF/TA grade 2-3). Results: uTr, uIgG positively correlated (p<0, 05) with TIF (r=0, 38, r=0, 43) and TA (r=0, 38, r=0, 45), respectively. We did not find correlations between uTr, uIgG and glomerulosclerosis. Using ROC-analysis all patients were separated in two groups using uTr or uIgG according to the degree of morphological lesions ("mild" or "severe) (Table 1, 2 ; Figure 1 ). According to the results of ROC-analysis we also found that all cut-off values of uTr, uIgG corresponded to the level of urinary protein excretion not more than 1, 25 g/24hour. Conclusion: Our results show that uTr and uIgG can be used as markers of early tubulointerstitial lesions in patients with IgA nephropathy with mild protein excretion.